1958
DOI: 10.1039/tf9585401537
|View full text |Cite
|
Sign up to set email alerts
|

The selective hydrogenation of acetylene

Abstract: A study has been made of the degree of selectivity of ethylene formation in the hydrogenation of acetylene catalyzed by rhodium, palladium, platinum and some palladium + silver mixtures supported on a-Al203. Analyses were performed by gasliquid chromatography.Palladium is the most active of the pure metals : prolonged exposure to hydrogen at room temperature decreases its activity for acetylene hydrogenation and completely destroys its activity for ethylene hydrogenation. The selectivity, before the onset of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
1
1

Year Published

1978
1978
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(70 citation statements)
references
References 0 publications
1
67
1
1
Order By: Relevance
“…Pd-based catalysts provide an outstanding activity and selectivity for the hydrogenation of alkynes [5][6][7][8]. However, they can act in selective as well as an unselective manner (for further discussion see SI).…”
Section: Introductionmentioning
confidence: 99%
“…Pd-based catalysts provide an outstanding activity and selectivity for the hydrogenation of alkynes [5][6][7][8]. However, they can act in selective as well as an unselective manner (for further discussion see SI).…”
Section: Introductionmentioning
confidence: 99%
“…The target improvement of these catalysts is to increase the selectivity to ethylene, raising the amount of ethylene gain and to force up the long term stability. 3 Firstly, Bond et al 4 reported about the use of Pd catalysts in selective hydrogenation of acetylene. A selective Pd catalyst was associated with small Pd ensembles which favor acetylene adsorption but 2 restrict ethylene adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…13,19,20 Another major issue in the acetylene hydrogenation is the selectivity to ethylene, since this reaction is performed industrially to remove acetylene impurities from ethylene feedstock. 21 The control of the oligomerization of acetylene, which causes the deactivation of the catalyst by covering the metal surface with polyolefin (green-oil) [22][23][24][25][26] is also important. The second part of this work presents the effect of the CNF-support acidity on the catalyst performance.…”
Section: Introductionmentioning
confidence: 99%